Development of STEAM Media to Improve Critical Thinking Skills and Science Literacy - Anik Twiningsih; Evi Elisanti (International Journal of Emerging Issues in Early Childhood Education, 2021)
The objective of this study is to develop STEAM-based learning media (Science, Technology, Engineering, Arts, Mathematics) in grade 1 thematic learning to improve critical thinking skills and the culture of scientific literacy in grade 1 students. This media was developed based on the STEAM approach, as the result of the use of media through the syntax of analizing, synthesizing, drawing conclusions, and organizing strategies and tactics. The excellence of this innovative work focuses on improving critical thinking skills and scientific literacy. This type of research is research and development (Research and Development) with ADDIE design (Analysis, Design, Development, Implementation, Evaluation). Based on the results of the study before using STEAM-based colored two-dimensional Figure Mixing media, it was identified that the mean class of students' critical thinking skills was 74.80 and the mean science literacy class was 73.61. After using STEAM-based typewriter media it can be identified that the mean class of students' critical thinking skills was 86.67 and the mean science literacy class was 88.67. The results of this study prove that STEAM-based non-typed media developed can improve students' critical thinking skills so that it has a positive impact on scientific literacy. This study concludes that new learning media developed can improve the activeness of students and ultimately have a positive impact on student learning outcomes.